SPORTS ACTIVITIES IN SCHOOL PHYSICAL EDUCATION: LIMITS AND CONVERGENCIES - Alves da Silva Neto, Manoel; Adeilton de Oliveira Andrade, Emanuel; Coutinho de Souza, Rubiana (Revista Gênero e Interdisciplinaridade, 2023)
The research discusses sports activity in school education, as well as contributions related to the cognitive and social aspects of students. It is based on the relevance that the practice of sport can contribute to the training of students. The objective is to discuss the limits and convergences of sports practice in school physical education, in an attempt to understand the influences of sports practice in school physical education for the social development of students. The research is bibliographic with qualitative aspects, the contributions were based on authors such as: Dias Et. Al. (2018), Common National Curriculum Base (2018), Gonzalez and Pedroso (2012), Almeida (2018), among others that covered the theme. As a result of the study, we revealed that sports practice positively influences the social, body and cognitive development of students, however, the limits were scored in the need for some schools to provide physical spaces and equipment suitable for sports, as well as if possible the school provide an assistant to the physical education teacher especially in school events and tournaments of sports activities outside the school.